Lacticaseibacillus rhamnosus P118 enhances host tolerance to Salmonella infection by promoting microbe-derived indole metabolites - Baikui Wang; Xianqi Peng; Xiao Zhou; Xiuyan Jin; Abubakar Siddique; Jiayun Yao; Haiqi Zhang; Weifen Li; Yan Li; Min Yue (eLife)
Salmonella is one of the most common foodborne pathogens, resulting in inflammatory gastroenteritis and frequently accompanied by dysbiosis. Gut commensals, such as Lactobacillus species, have been proven to exhibit broad antibacterial activities and protect hosts against pathogenic infections. Here, Lacticaseibacillus rhamnosus strain P118, screened from 290 isolates recovered from fermented yogurts and healthy piglet intestines using traditional and Caenorhabditis elegans-infection screening strategies, exerts great probiotic properties. Notably, P118 and its supernatant exhibited great antibacterial activities and attenuated C. elegans susceptibility to Salmonella infection. We found that P118 protected mice against Salmonella lethal infections by enhancing colonization resistance, reducing pathogen invasion, alleviating intestinal pro-inflammatory response, and improving microbial dysbiosis and fecal metabolite changes. Microbiota and fecal metabolome analyses suggested P118 administration significantly decreased the relative abundances of potentially harmful microbes (e.g., Salmonella, Anaeroplasma, Klebsiella) and increased the fecal levels of tryptophan and its derivatives (indole, indole-3-acrylic acid, 5-hydroxytryptophan, 5-methoxyindoleacetate). Deterministic processes determined the gut microbial community assembly of P118-pretreated mice. Integrated omics further demonstrated that P118 probiotic activities in enhancing host tolerance to Salmonella infection were mediated by microbe-derived tryptophan/indole metabolites (e.g., indole-3-acrylic acid, indole, tryptophan, 5-methoxyindoleacetic acid, and 5-hydroxytryptophan). Collective results demonstrate that L. rhamnosus P118 could enhance host tolerance to Salmonella infections via various pathways, including direct antibacterial actions, inhibiting Salmonella colonization and invasion, attenuating pro-inflammatory responses of intestinal macrophages, and modulating gut microbiota mediated by microbe-derived indole metabolites.